Perancangan Media Informasi Profil Kantor Desa Muara Bengkal Ilir Menggunakan Content Management System (CMS) - Seftiani Nur; Puput Alpria Nina; Fahreza Agung Firmansyah; Abdul Rahim (Jurnal Pengabdian Kepada Masyarakat, 2023)
The development of information and communication technology has had a significant impact in various sectors of life, including in the provision of public information. The importance of quick and easy access to information by the community is the main basis for the Muara Bengkal Ilir Village Head to utilize technology as an effective means of communication. To overcome these problems, we provide a solution to create a WordPress-based Muara Bengkal Ilir Village Office Profile website. The flow of implementing this service is a field study, problem identification, website creation, and testing. The main result of this service is a Muara Bengkal Ilir Village Office Profile Website as an official website in helping disseminate information on the Muara Bengkal Ilir Village Office Profile